Evidence of the absence poetry notebook of some of the Azerbaijan Poets - Alireza Mozaffari, Morteza Zolfegari Garahasanloo, Abdolnaser Nazaryani (Opción, 2019)
In this research, it was tried to draw attention to the lack of Persian poetry in Azerbaijan and, based on the arguments and existing evidence and, finally, referring to libraries and online databases and exploring manuscripts and the list of printed books of libraries and references; the validity of some of the poets is proved. As a result, Mohseni Ardebili is a poet whose name appears only in the Samii sermon. In conclusion, it seems that the beginning of more and more studies on other poets in the regions of Iran seems to be significant.